Anti-biofouling properties of poly(dimethyl siloxane) with RAFT photopolymerized acrylate/methacrylate surface grafts against model marine organisms. Issue 1 (13th January 2021) - Kuliasha, Cary A.; Fedderwitz, Rebecca L.; Stafslien, Shane J.; Finlay, John A.; Clare, Anthony S.; Brennan, Anthony B.
Abstract: Biofouling of man-made surfaces by marine organisms is a global problem with both financial and environmental consequences. However, the development of non-toxic anti-biofouling coatings is challenged by the diversity of fouling organisms. One possible solution leverages coatings composed of diverse chemical constituents. Reversible addition-fragmentation chain-transfer (RAFT) photopolymerization was used to modify poly(dimethylsiloxane) (PDMSe) surfaces with polymeric grafts composed of three successive combinations of acrylamide, acrylic acid, and hydroxyethyl methacrylate. RAFT limited conflicting variables and allowed for the effect of graft chemistry to be isolated. While all compositions enhanced the anti-biofouling performance compared with the PDMSe control, the ternary, amphiphilic copolymer was the most effective with 98% inhibition of the attachment of zoospores of the green alga Ulva linza, 94% removal of cells of the diatom Navicula incerta, and 62% removal of cells of the bacterium Cellulophaga lytica . However, none of the graft compositions tested were able to mitigate reattachment of adult barnacles, Amphibalanus amphitrite .